Sorafenib-Induced Autophagy Promotes Glycolysis by Upregulating the p62/HDAC6/HSP90 Axis in Hepatocellular Carcinoma Cells - Xiaoyu Yan; Xiaoyu Yan; Rui Tian; Rui Tian; Jicheng Sun; Yuanxin Zhao; Buhan Liu; Jing Su; Minghua Li; Minghua Li; Wei Sun; Wei Sun; et al. (Frontiers Media S.A., 2022)
Sorafenib has attracted much attention as the first drug approved by the FDA for the treatment of advanced hepatocellular carcinoma (HCC). Because of the drug tolerance, the overall outcomes were far from satisfactory. Current studies suggest that changes in glucose metabolism induced by sorafenib are the pivotal resistant mechanism of HCC cells, but the specific regulatory mechanism remains unclear, which makes it difficult to increase drug sensitivity by targeting glycolysis. As a metabolic-recycling pathway, autophagy regulates multiple important pathways involved in cell survival and death. In this study, we found the expression of key autophagy proteins were closely related to the prognosis and progression of HCC patients. Based on in vitro experiments, our studies showed sorafenib induced autophagy in HCC cells. Inhibition of autophagy by chloroquine could significantly increase the sensitivity of HCC cells to sorafenib and reverse the enhancement of glycolysis. Furthermore, sorafenib-induced autophagy promoted the deacetylase activity of HDAC6 by degrading p62, which promoted the activity of PKM2 by regulating the acetylation of its critical substrate HSP90. In this study, we investigated the role of autophagy-induced HDAC6 in regulating the key glycolytic enzyme PKM2, which may be helpful to clarify the relationship between autophagy and glycolysis in a sorafenib-resistant mechanism. Targeting p62/HDAC6/HSP90 could herald a potential improvement in HCC therapy.